Mosquitoes of peridomiciliary and extradomiciliary environments in of southern Brazil - Teodoro, Uelsei; Guilherme, Ana Lúcia Falavigna; Lozovei, Ana Leuch; La Salvia Filho, Vicente; Sampaio, Adelbar Antonio; Spinosa, Roberto Palma; Ferreira, Maria Eugênia Moreira Costa; Barbosa, Orlando Carlos; Lima, Edson Maurício de (Revista de Saúde Pública, 1994)
Mosquitoes were collected on Sonho Real farm, Querência do Norte county, Paraná State, Brazil, using human bait and Falcão traps between June 1989 and May 1990. The fauna composition, monthly density, hours of major density, human attraction and presence of mosquitoes in domestic animal shelters were investigated. 5,923 mosquitoes of the genera Aedes, Aedomyia, Anopheles, Coquillettidea, Culex, Mansonia, Psorophora, Sabethes and Uranotaenia were collected. 33 species of mosquitoes were identified and among them Aedes scapularis, Anopheles albitarsis, Aedomyia squamipennis, Coquillettidea lynchi, Mansonia titillans e Coquillettidea venezuelensis were predominant. All these species were captured mainly on human bait, except Aedomyia squamipennis that was captured in domestic animal shelters. With regard to all the mosquitoes captured (5,923), their major period of activity was between 18 and 19 hours and April was the month of greatest density.